The Potential of Clinical Pastoral Education in Facilitating Contextual, Effective and Affordable Pastoral Ministry for Impoverished Black Communities in South Africa - Buffel, O. A. (Black theology, 2022)
Clinical Pastoral Education is an important part of an educational process of pastoral ministry. It is also a gift that can potentially contribute meaningfully to facilitating contextual, affordable pastoral ministry for Black communities in South Africa. This article argues that for CPE to have space and a future it must be contextual and liberating. It must respond appropriately to the conditions, realities and needs of Black communities who bear the brunt of poverty and associated socio-economic-cultural and conditions. In the U.S.A context, CPE has always been a response to the conditions, realities and needs of the Americans. Equally, in the South African context, CPE cannot afford to ignore “the living human documents” (the living human web), whose realities are different from those of Americans. CPE must acknowledge that it is part of the broader field of pastoral care, which is based on Western-dominated theories. It must be inclusive and listen carefully to Black communities.